EFFECT OF TEACHERS’ TASKS PRACTICES ON STUDENTS’ ACHIEVEMENT IN MATHEMATICS - Sanni, Rasheed (Sokoto Educational Review, 2012)
What students do in the classroom during lessons is/are largely determined by the tasks that are set up and implemented by the teacher, and expectedly impact on the students’ learning achievement. The researcher explores how task selection and implementation practices of the teacher affect students’ achievement. The study employed quasi-experimental research – two-group pre-test and post-test design was used. Both experimental and control groups were SS 1 (science groups) in their respective schools in Lagos State. Pretest and posttest consist of a collection of question items from past relevant examinations and Mathematics Olympiad questions. The regular mathematics teacher taught in the control group; while in the experimental group, the students were taught by their teacher but with technical support from the researcher on tasks selection and implementation. Data was analysed on two levels, using descriptive and inferential statistics. Results show that (1) learners in the control group performed statistically significantly better in the pre-test; (2) there was no statistically significant difference in the performance of learners in the two groups at posttest. Descriptive statistics, however, shows that the performance of learners in the experimental group was better than that of those in the control group. These results were discussed, implications for instructional practice, for teacher training and development were provided.